The Documentation of COVID-19 Pandemic in Malaysia using 2D Animation - Suhaili Din; Nur Aliffa Abdul Jalil (Journal of Computing Technologies and Creative Content, 2022)
World nowadays is being attacked with a corona disease which has been named as COVID-19 by World Health Organization. COVID-19 killed millions of people around the world and Malaysia. Some of the people are still lack of information about how dangerous this disease and disregard about this matter is. Nowadays there are Standard Operating Procedure (SOP) that has been made by government in Malaysia. The objectives of this project are to produce three 2D animation videos as the documentation approach for historical archive of COVID-19 in Malaysia and lastly to evaluate the effectiveness of the 2D animation videos as the documentation approach used for documenting COVID-19 in Malaysia as historical event archive. These animated series are created by first using Adobe Illustrator to create the illustrations, then moving on to Adobe After Effects to create the animation based on the illustrations, and finally Adobe Premiere to create the videos by combining all the animations. All three animated series will be uploaded on YouTube channel as the platform of storage and viewing. ADDIE Model is the methodology used by researcher to develop the project. The evaluation of the animated series was carried out online via Google Form with the total of 50 respondents. Based on the survey, 70% from the respondents were satisfied with the information provided in the animated series.